Journal de la création - Huston, Nancy (Actes sud, 2001)
Pendant des millénaires, tout paraissait simple : aux hommes la création, aux femmes la procréation ; aux hommes l'esprit et aux femmes le corps. L'émancipation féminine a bousculé cette distribution des rôles et mis à mal des métaphores séculaires : la muse féminine, l'œuvre d'art comme amante ou comme " enfant " de l'artiste. Mais trouver un nouveau modus vivendi n'est pas facile pour autant. Mettant à profit une certaine et curieuse forme de clairvoyance liée, dans son esprit, aux métamorphoses de son corps de femme enceinte, Nancy Huston s'est penchée sur les histoires souvent douloureuses de Sand et Musset, Virginia et Leonard Woolf, Scott et Zelda Fitzgerald, Sartre et Beauvoir. Le récit de ses recherches sur les couples d'écrivains et le journal de sa propre grossesse se croisent, se répondent et se complètent pour évoquer les mystères de l'amour, de l'inspiration, du couple et de la création.
Donné en lecture : 11-56
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; cours; création; discipline; europe; fem1000; littérature; premier cycle; procréation; périodes historiques; régions géographiques; santé; santé reproductive; thématiques; études littéraires

Women in Dada: essays on sex, gender, and identity - Sawelson-Gorse, Naomi (The MIT Press, 2001)
Finally, a look at the role of women in the shaping of the high-spirited—but hardly feminist—Dada monement. For all of its iconoclasm, the Dada spirit was not without repression, and the Dada movement was not without misogynist tendencies. Indeed, the word Dada evokes the idea of the male—both as father and as domineering authority. Thus female colleagues were to be seen not heard, nurturers not usurpers, pleasant not disruptive.This book is the first to make the case that women's changing role in European and American society was critical to Dada. Debates about birth control and suffrage, a declining male population and expanding female workforce, the emergence of the New Woman, and Freudianism were among the forces that contributed to the Dadaist enterprise. Among the female dadaists discussed are the German émigré Baroness Elsa von Freytag-Loringhoven; Berlin dadaist Hannah Höch; French dadaists Juliette Roche and Suzanne Duchamp; Zurich dadaists Sophie Taeuber and Emmy Hennings; expatriate poet and artist Mina Loy; the "Queen of Greenwich Village," Clara Tice; Margaret Anderson and Jane Heap, the lesbian couple who ran The Little Review; and Beatrice Wood, who died in 1998 at the age of 105. The book also addresses issues of colonialist racism, cross-dressing and dandyism, and the gendering of the machine. The bibliography was compiled by the International Dada Archive (Timothy Shipe and Rudolf E. Kuenzli). Contributors Eleanor S. Apter, Barbara J. Bloemink, Willard Bohn, Carolyn Burke, William A. Camfield, Whitney Chadwick, Dorothea Dietrich, Susan Fillin-Yeh, Paul B. Franklin, Renée Riese Hubert, Marisa Januzzi, Amelia Jones, Marie T. Keller, Rudolf E. Kuenzli, Maud Lavin, Margaret A. Morgan, Dickran Tashjian, Elizabeth Hutton Turner, Barbara Zabel
Keywords: 1900-1999; 1910-1919; allemagne; amériques; approches et analyses; arts; cours; discipline; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; régions géographiques; sexisme; suisse; systèmes d'oppressions; thématiques; états-unis

Réécriture de l'histoire, altérité et identité dans le roman Moi, Tituba sorcière de Maryse Condé (1986) - Tamiozzo, Josée (Université du Québec à Montréal, 2001)
Keywords: 1900-1999; 1980-1989; 1990-1999; IREF; arts; discipline; europe; france; mémoires/thèses; périodes historiques; régions géographiques; sorcière; thématiques; écriture des femmes*; études littéraires

Les femmes anglaises - Tristan, Flora (Promenades dans Londres : L'aristocratie et les prolétaires anglais (1840), 2001)
Keywords: 1800-1899; arts; classe ouvrière; cours; discipline; europe; fem1000; histoire et politique; littérature; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques; études littéraires

Lesbian empire: Radical crosswriting in the Twenties - Wachman, Gay (Rutgers University Press, 2001)
Gay Wachman provides a critical new reading of sexually radical fiction by British women in the years during and after the First World War. She contrasts works by Sylvia Townsend Warner, Virginia Woolf, Rose Allatini, and Evadne Price with more politically and narratively conservative novels by Radclyffe Hall and Clemence Dane. These writers, she states, formed part of an alternative modernist tradition that functioned both within and against the repressive ideology of the British Empire, using fantasy as a means of reshaping and critiquing a world fragmented by war. Wachman places at the center of this tradition Sylvia Townsend Warner's achievement in undermining the inhibitions that faced women writing about forbidden love. She discusses Warner's use of crosswriting to transpose the otherwise unrepresentable lives of invisible lesbians into narratives about gay men, destabilizing the borders of race, class, and gender and challenging the codes of expression on which imperialist patriarchy and capitalism depended.
Keywords: amour interdit; approches et analyses; arts; discipline; europe; littérature; patriarcat; personnes lesbiennes; racisme; royaume-uni; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; transgression; études littéraires